2022
DOI: 10.3390/fishes7060301
|View full text |Cite
|
Sign up to set email alerts
|

The Rich Get Stronger: The Purse Seine Fishery of the Turkish Straits System

Abstract: Purse seiners generally try to maximize their revenues by targeting multiple species, starting with the most valuable ones available. The technology and capacity of purse seiners can be exceptionally high for the stocks found in the Marmara Sea, Turkey’s only inland sea, due to its small size and nearly totally enclosed nature. Due to their large capabilities, they are responsible for the majority of catches and hence declines from this sea and thus should be held responsible for the poor state of marine stock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Cultural assets, such as the local wisdom of no-fishing, can be empowered to achieve long-term financial well-being for the community, ecological sustainability in the form of freshwater fish stock availability, and long-term sustainability of the local wisdom of no-fishing itself. As local wisdom is a concept, an idea and ideas that are always passed on to the next generation so that harmony is built in the management of life and its environment, it becomes a link from one generation to the next (9,10,11), subsequent research shows that local people as beneficiaries directly related to fish resources when working with local governments are generally more effective in achieving the expected results, so that community participation is an important factor in the management of protected areas and the sustainability of fish resources (12,13). Subsequent research has found that local communities benefit when they participate and play their role in resource management through their traditional knowledge to formulate sustainable management strategies.The role of culture in the use of natural resources places cultural capacities, knowledge and technology systems, religion, traditions and social capital (ethics and environmental wisdom, norms and legal institutions) as important in the context of resource use.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural assets, such as the local wisdom of no-fishing, can be empowered to achieve long-term financial well-being for the community, ecological sustainability in the form of freshwater fish stock availability, and long-term sustainability of the local wisdom of no-fishing itself. As local wisdom is a concept, an idea and ideas that are always passed on to the next generation so that harmony is built in the management of life and its environment, it becomes a link from one generation to the next (9,10,11), subsequent research shows that local people as beneficiaries directly related to fish resources when working with local governments are generally more effective in achieving the expected results, so that community participation is an important factor in the management of protected areas and the sustainability of fish resources (12,13). Subsequent research has found that local communities benefit when they participate and play their role in resource management through their traditional knowledge to formulate sustainable management strategies.The role of culture in the use of natural resources places cultural capacities, knowledge and technology systems, religion, traditions and social capital (ethics and environmental wisdom, norms and legal institutions) as important in the context of resource use.…”
Section: Resultsmentioning
confidence: 99%